2

(1)

等价于 $$ \begin{aligned} &\lim_{x\to1}\frac{x^n-1}{x^m-1}\\ =&\lim_{t\to0}\frac{(t+1)^n-1}{(t+1)^m-1}\\ =&\lim_{t\to0}\frac{t^n+nt+o(t)}{t^m+mt+o(t)}\\ =&\lim_{t\to0}\frac{t^{n-1}+n+o(1)}{t^{m-1}+m+o(1)}\\ =&\frac{n}{m} \end{aligned} $$

(2)

令 $1+\alpha x=t^m$ 可得 $$ \lim_{t\to 1}\frac{\alpha(t-1)}{t^m-1}=\frac{\alpha}{m} $$

(3)

$$ \lim_{x\to0}\frac{\sqrt[m]{1+\alpha x}-\sqrt[n]{1+\beta x}}{x}=\lim_{x\to0}\frac{\sqrt[m]{1+\alpha x}-1}{x}-\lim_{x\to0}\frac{\sqrt[n]{1+\beta x}-1}{x}=\frac{\alpha}{m}-\frac{\beta}{n} $$

(4)

原式等价于

$$ \prod_{i=1}^{n}\lim_{x\to1}\frac{1-\sqrt[i]{x}}{1-x}=\prod_{i=1}^n\frac{1}{i}=\frac{1}{n!} $$

3

(7)

在我手上这个版本中是 $x\to+\infty$ , 实际上应该是 $n\to+\infty$​.

$$ \lim_{n\to\infty}n\left(\cos\left(\frac{x}{\sqrt{n}}\right)-1\right) $$ 等价于 $$ \lim_{t\to0}x^2\frac{\cos(t)-1}{t^2} $$

由于 $\cos(t)-1\sim-\frac{1}{2}t^2$ , 结果为 $\frac{-x^2}{2}$ .

4

$$ \lim_{n\to\infty}n\frac{\sum_{i=1}^nx^i}{n}=\lim_{n\to\infty}\sum_{i=1}^nx^i=\lim_{n\to\infty}\frac{x-x^{n+1}}{1-x}=\frac{x}{1-x} $$